The focus of attention is similar to other memory systems rather than uniquely different - Beaudry, Olivia; Neath, Ian; Surprenant, Aimée M.; Tehan, Gerald (Frontiers in Human Neuroscience, 2014)
According to some current theories, the Focus of Attention, part of working memory, represents items in a privileged state that is more accessible than items stored in other memory systems. One line of evidence supporting the distinction between the focus of attention and other memory systems is the finding that items in the focus of attention are immune to proactive interference (when something learned earlier impairs the ability to remember something learned more recently). The focus of attention, then, is held to be unique: it is the only memory system that is not susceptible to proactive interference. We review the literature used to support this claim, and although there are many studies in which proactive interference was not observed, we found more studies in which it was observed. We conclude that the focus of attention is not immune to proactive interference: items in the focus of attention are susceptible to proactive interference just like items in every other memory system. And, just as in all other memory systems, it is how the items are represented and processed that plays a critical role in determining whether proactive interference will be observed.